Respuesta :
Answer:
let's use x to represent the unknown number
and let y=3
solution
x+y=9
x+3=9
x=9-3
x=6
therefore 6 is the unknown number
so
6+3=9
Answer:
- The required values are 6 and 3.
Step-by-step explanation:
Let the numbers be x and y. Now, We have to follow the question's statement. First of all, we have to form equations according to the question's statement.
- x + y = 9
- x - y = 3
Solve the question by elimination method.
- x + y = 9
- x - y = 3
_______________
- 2y = 6
- y = 6/2
- y = 3
Put the value of y in equation 1.
- x + y = 9
- x + 3 = 9
- x = 9 - 3
- x = 6
Therefore, the required values are 6 and 3.